A Stable Routing Protocol for Vehicles in Urban Environments - Hyun Yu; Sanghyun Ahn; Joon Yoo (International Journal of Distributed Sensor Networks)
The vehicular ad hoc network (VANET) is an essential technology that enables the deployment of the intelligent transportation system (ITS), which improves the traffic safety and efficiency. For the efficient message delivery in VANETs, it is desirable to provide a reliable and stable VANET routing protocol. However, VANET routing is challenging since the VANET is fundamentally different from conventional wireless ad hoc networks; vehicles move fast, and the network topology changes rapidly, causing intermittent and dynamic link connectivity. In this paper, we propose a VANET routing protocol that works based on the real-time road vehicle density information in order to provide fast and reliable message delivery so that it can adapt to the dynamic vehicular urban environment. In the proposed mechanism, each vehicle computes the real-time traffic density of the road to which it belongs from the beacon messages sent by vehicles on the opposite lane and its road information table. Using the road traffic density information as a routing metric, each vehicle establishes a reliable route for packet delivery. We compare our proposed mechanism with the well-known GPSR via NS-2 based simulations and show that our mechanism outperforms GPSR in terms of both delivery success rate and routing overhead.